Nilai C/R sebagai Indikator Keberhasilan Pada Program Inseminasi Buatan di Distrik Semangga - irianti Timaubas; Nurcholis Nurcholis; Dirwan Muchlis (Musamus Journal of Livestock Science, 2023)
This study aims to determine the success of artificial insemination in the Semangga district with the Conception/rate indicator. The method used for determining the sample using pourpose sampling as many as 45 respondents spread over 4 villages in the Semango district. Primary and secondary data are collected for further analysis. Data analysis was carried out descriptively and averaged using a standard deviation. The results showed that the R/C was 71.83 which means that the success rate of bolt insemination in Semango district is quite high.